Komunikasi Pelayanan Masyarakat Komunitas Edan Sepur dalam Menjaga Keselamatan Pelintas Rel - Resty Zulia Latifah; Anne Maryani (UNISBA Press, 2024)
Abstract. Service is an effort to help and meet the needs of individuals or groups. Services can be provided through communities, one of which is the